2021
DOI: 10.1029/2021jg006402
|View full text |Cite
|
Sign up to set email alerts
|

Does Photomineralization of Dissolved Organics Matter in Temperate Rivers?

Abstract: Dissolved organic matter (DOM) is one of the largest fluxes of carbon in inland water ecosystems and a central component of riverine metabolism. DOM, which is approximately 50% dissolved organic carbon (DOC) by mass (Dittmar & Stubbins, 2014;Krogh, 1934), is a nutrient and energy source, capable of transporting metals and pollutants, and a driver of light availability in water bodies (Kaplan & Cory, 2016;Schlesinger & Melack, 1981). Large amounts of riverine DOC enter the ocean annually, where it is an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…DOC ts ${t}_{s}$ measured from 20 combined photooxidation/bioassays were comparatively much lower (median: 314 hr) (Figure 8), indicating quicker mineralization when considering in situ photo‐ and biotic oxidations together. Particularly, photodegradation is a widely recognized process that promotes microbial breakdown (Allesson et al., 2016; Lu et al., 2013) though either photo‐ or microbial oxidation alone is insignificant for DOC removal in river networks (del Giorgio & Pace, 2008; Maavara et al., 2021). DOC vf ${v}_{f}$ chosen for Da scaling in this analysis (0.038 m d −1 , corresponding of a ts ${t}_{s}$ of 720 hr or WRT of a 6–7 order river network) (Wollheim et al., 2015) falls between DOC uptake determined from the solute addition and dark bioassay methods (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DOC ts ${t}_{s}$ measured from 20 combined photooxidation/bioassays were comparatively much lower (median: 314 hr) (Figure 8), indicating quicker mineralization when considering in situ photo‐ and biotic oxidations together. Particularly, photodegradation is a widely recognized process that promotes microbial breakdown (Allesson et al., 2016; Lu et al., 2013) though either photo‐ or microbial oxidation alone is insignificant for DOC removal in river networks (del Giorgio & Pace, 2008; Maavara et al., 2021). DOC vf ${v}_{f}$ chosen for Da scaling in this analysis (0.038 m d −1 , corresponding of a ts ${t}_{s}$ of 720 hr or WRT of a 6–7 order river network) (Wollheim et al., 2015) falls between DOC uptake determined from the solute addition and dark bioassay methods (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…DOC cycling in river networks involves multiple processes that contribute simultaneously to its gains/losses within rivers (Battin et al., 2008; Bernhardt et al., 2018; Kaplan & Cory, 2016). In situ photooxidation (Maavara et al., 2021) and biotic mineralization (del Giorgio & Pace, 2008; Raymond & Bauer, 2000) are the two main processes contributing to permanent DOC removal and CO 2 emission from river systems. The magnitude of DOC removal rate in river networks is however difficult to quantify due to the complex interplays among multiple biotic/abiotic processes that contribute to DOC concentration variations in spatially distributed river networks (Lv et al., 2019; Wollheim et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Despite having shown that photomineralization can be important in river networks relative to biomineralization, its importance is close to negligible relative to the magnitude of DOC fluxes in both lakes and rivers. Maavara et al (2021) considered the importance of photomineralization in the Connecticut River watershed's river reaches in terms of its ability to eliminate DOC from the water column and found that per‐reach removal ( R i , Eq. 13) was 0.026–0.18% of the DOC flux at median flows.…”
Section: Model Output and Discussionmentioning
confidence: 99%
“…Complete photooxidation of DOC to dissolved inorganic carbon (DIC) (i.e., photomineralization, ψ), in each river reach and lake segment is based on the formulation (Koehler et al 2012;Cory and Kling 2018;Maavara et al 2021):…”
Section: Photomineralizationmentioning
confidence: 99%
See 1 more Smart Citation